Evaluation of Knowledge on Emergency Management of Avulsed Teeth Among Turkish Medical and Dental Students - Gulsum Duruk; Ismail Cuneyt Daşkıran (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the knowledge of medical and dental students regarding the emergency management of avulsed teeth. Material and Methods: This cross-sectional survey study was performed on 1841 students. Medical (n=746) and dental (n=845) students from different universities were included in this study. A questionnaire about the emergency management of avulsed teeth was conducted on the students. Also, 250 medical students from 3rd grade were included in the study and trained. The questionnaire was applied twice, before and after the training on the subject. Results: The mean correct answer scores were similar among the medical students in different grades (p>0.05). There were no statistically significant differences between the trained medical students and clinical dental students' correct answer scores, but there was a significant difference between the pre-clinical (1st-2nd-3rd years) and clinical (4th-5th years) dental students (p<0.01). Conclusion: Medical and preclinical dental students had lack of knowledge about the emergency management of avulsed teeth, while clinical dental and trained medical students were very knowledgeable. This result indicates the importance of education.